Originally Posted by
alex95 Can someone please tell me what I am doing wrong in the following calculation:
x^4 + sqrt(3)*x^2 - 3 = 0
sqrt(3)*x^2 = 3 - x^4 // I square all terms to get rid of the root
3x^4 = 9 - x^8 // u = x^4
3u = 9 - u^2
-u^2 - 3u + 9
//Using the quadratic formula to solve this
[-(-3) +- sqrt((-3)^2 - 4(-1)(9))] / -2
[3 +- sqrt(9 + 36)] / -2
[3 +- sqrt(45)]/-2
(3 +- 6.71) / -2
u = (3 + 6.71) / -2 = -4.86
u = (3 - 6.71)/-2 = 1.86
The solution is supposed to be 1.03. I have tried to solve this several ways but somewhere I am going wrong. Any advice is really appreciated. Thanks in advance